2007
DOI: 10.1002/hyp.6803
|View full text |Cite
|
Sign up to set email alerts
|

Land management impacts on runoff sources in small Amazon watersheds

Abstract: Abstract:Forest clearing and conversion to cattle pasture in the lowland Amazon region has been linked to soil compaction and increased soil water storage, which combine to diminish soil infiltration, enhance quick lateral flows and increase the stream flow response to precipitation. Quantifying the importance of quick surficial flow in response to this land use change requires identification of water sources within catchments that contribute to stream flow. Using an end member mixing analysis approach, potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
3
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 51 publications
6
107
3
5
Order By: Relevance
“…[25][26][27] In fact, Williams et al and Chaves et al studying intact forests in Central Amazonas and Rondônia, respectively, found more acidic pH values (4.7 and 5.2) than those observed in the Urupá basin. 15,16 In addition to the above mentioned factors influencing acidity in groundwater, in rural and urban areas, domestic and industrial sewage disposal and soil alteration through corrective products and fertilizers can also influence pH. 28 Hence, the proximity of wells to septic tanks could have led to the differences observed between the two riversides, mainly for the shallower wells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27] In fact, Williams et al and Chaves et al studying intact forests in Central Amazonas and Rondônia, respectively, found more acidic pH values (4.7 and 5.2) than those observed in the Urupá basin. 15,16 In addition to the above mentioned factors influencing acidity in groundwater, in rural and urban areas, domestic and industrial sewage disposal and soil alteration through corrective products and fertilizers can also influence pH. 28 Hence, the proximity of wells to septic tanks could have led to the differences observed between the two riversides, mainly for the shallower wells.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies conducted in forest ecosystems in the Amazon region have also found low conductivity values. 15,16 Concentrations of chemical constituents in groundwater showed high spatial variability, especially for anions ( Figure 1). The general order of dominance of cations in the groundwater of the studied area is Na + >> K + ≈ Ca 2+ > Mg 2+ and Ca 2+ > Na + > Mg 2+ > K + for right and left margins, respectively, whereas for anions it is Cl -> HCO 3 -≈ NO 3 ->> SO 4 2-(right) and HCO 3 ->> NO 3 -≈ Cl ->> SO 4 2-(left).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Chaves et al (2008), o desmatamento e a conversão em pastagem na região amazônica estão diretamente relacionados à compactação do solo e ao aumento de armazenamento hídrico, o que combina com a diminuição da infiltração da água no solo e com o aumento da inundação lateral e da velocidade de resposta do escoamento à precipitação. Assim, para mitigar os efeitos da pecuária extensiva na bacia hidrográfica, pode ser empregada a técnica de terraceamento ou sulcamento para permitir melhor infiltração da água e, com isso, a recarga do lençol freático e a diminuição da inundação.…”
Section: Discussionunclassified
“…The effect of human activities on runoff regimes has been proven by a number of experimental studies from various parts of the world. Much research has focussed on monitoring the influence of changes in land cover, mainly deforestation and afforestation processes [4,5,11,26], the influence of cultivated areas [13,15,20] and the impact of logging [6,22,28].…”
Section: Introductionmentioning
confidence: 99%